PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA CALON GURU MATEMATIKA MELALUI PEMBELAJARAN PROJECT-BASED LEARNING (PjBL) PADA MATERI STATISTIKA: Improvement of Prospective Mathematics Teachers' Critical Thinking Skills through Project-Based Learning (PjBL) on Statistics Materials - Anjariyah, Deka (Aksioma, 2023)
To equip prospective mathematics teacher students in solving problems faced both in class and outside the classroom, one of the abilities that need to be improved is critical thinking skills. Critical thinking skill is a high-order thinking skill (HOTS) that is important for students to master because it can place students in charge of reasonable situations or integrate new ideas with previous knowledge. This study aims to describe whether project-based learning (PjBL) in statistics material can improve the critical thinking skills of prospective mathematics teacher students. This research is a class action research with ten students from the class of 2021 as research subjects. The stages in this research are in the form of spiral cycles which include activities (1)planning, (2)implementing actions, (3)observation, and (4)reflection. The research instrument used was a critical thinking skill test and observation sheets for lecturer and student activities. The results of the study show that (1) the use of the PjBL learning model can improve the critical thinking skills of prospective mathematics teacher students class of 2021, as evidenced by the results of the critical thinking test with an increase in the percentage of students who scored a minimum of 76 (B) in the first cycle by 50% to 90 % in the second cycle and (2) the use of the PjBL learning model can increase student learning activity, indicated by an increase in the percentage of student activity from the first cycle of 78% to 85% in the second cycle.